Analysis Of Waiting Time For Scheduling Elective Surgery For Oncology Patients : Literature Review - Devi Setyawati; Pujiyanto Pujiyanto (International Journal Labs, 2025)
Scheduling of elective surgery in oncology surgery patients is an important factor in determining the effectiveness of services and clinical outcomes. This paper aims to review the analysis of waiting time for elective surgery in oncology patients based on a literature review of the ProQuest, Scopus, and Google Scholar databases. Article selection was carried out using PICOS-based inclusion criteria and the PRISMA method. The review results showed that there was a variation in waiting time based on the type of cancer, with breast cancer patients generally having shorter waiting times than colorectal or cervical cancer. The implementation of a structured scheduling system has been shown to be effective in reducing waiting times by 15–30% compared to conventional scheduling, as well as improving patient satisfaction and experience. Factors such as multidisciplinary team collaboration, utilization of information technology, and operating room management are key to successful scheduling. However, challenges such as limited resources and system adaptation are still found. This review emphasizes the importance of optimizing the scheduling system to accelerate access to surgery and improve outcomes for oncology surgery patients.